Gut microbiome and metabolome library construction based on age group using short-read and long-read sequencing techniques in Korean traditional canine species Sapsaree - Son, Seon-Hui; Kang, Min-Geun; Kang, Anna; Kang, Yonggu; Kim, Kimoon; Kwak, Min-Jin; Song, Minho; Kim, Younghoon (Frontiers in Microbiology, 2024)
This study investigated age-related changes in the gut microbiota and metabolome of Sapsaree dogs through metagenomic and metabolomic analyses. Using Illumina (short-read) and Nanopore (long-read) sequencing technologies, we identified both common and unique bacterial genera in the dogs across different age groups. In metagenomic analysis, Firmicutes were predominant at the family level. At the genus level, Lactobacillus, Streptococcus, Romboutsia, and Clostridium XI were the most abundant, and the bacterial genera typically considered beneficial were less prevalent in senior dogs, whereas the genera associated with pathogenicity were more abundant. These findings suggest age-related shifts in gut microbiota composition. Metabolomic analysis showed distinct clustering of metabolites based on the age group, with changes in metabolite profiles correlating with metagenomic findings. Although Illumina and Nanopore methods provided distinctive results, the genera detected by both methods exhibited similar trends across all age groups in Sapsaree dogs. These findings highlight the relationship between ages, metabolite profiles and gut microbiota composition in dogs, suggesting the need for further research to explore this relation in greater depth.